Project for a New Evangelization of the Archiepiscopal Syro-Malabar Church - Loda, Natale (Iustitia, 2012)
Dr. Natale Loda treats the following main points: 1. Missionary activity, 2. The Missionary Vocabulary, 3. The New Evangelization, 4. The Evangelization of the People in CCEO, 5. The Missionary Action and Evangelization in the Pastor Bonus and the Oriental Churches. The Problematic of Territoriality, 6. On the Intermediary Solution of the Holy See with Respect to the Problematic of the Territoriality and Personality Coinciding with the Missionary Right, and 7. Prospectives for a New Evangelzation of the Syro-Malabar and Syro-Malankara Churches.